PARENTS’ PERCEPTION OF PRESCHOOL EDUCATION AND THEIR ROLE IN CHILDREN’S EARLY LEARNING: PARENTS’ PERCEPTION OF PRESCHOOL EDUCATION AND THEIR ROLE IN EARLY LEARNING - GRACE ANN MATHEW; NISHA VIKRAMAN (The Journal of Research ANGRAU, 2026)
The present study was carried out in 2023 and adopted a quantitative research design to assess parents perception on preschool education and their involvement in children’s early learning. The area selected for the study was Ernakulam district of Kerala and the sample was 400 parents of 3 to 6-year-old children attending either preschool or Anganwadi that were selected through stratified random sampling. The findings showed that parents highly value preschool education and desire meaningful involvement, yet remain doubtful about giving early academic instruction. 80% of respondents agreed or strongly agreed that preschool is crucial. Strengthening parent–teacher partnerships, providing parental training on developmentally appropriate practices, and fostering opportunities for parents’ participation may help bridge this gap.